Importance of references’ science in information and library studies - Anaswah , Mohmad (Dirasat: Human and Social Sciences, 2022)
The research aims to explore the value of reference terms and its added value, and this by identifying the reference term opposite to bibliography term that has been restored to its origins in Arabic language, and its approval by the councils of the Arabic language and its display in Arab intellectual production. The documentary approach was used to achieve the goals of this research, which was one of its most prominent results, to reach that there is a disparity in understanding what is the reference term and its awareness and definition. The research concluded that the reference term is the Arab equivalent of the term bibliography, and the term of references as opposed to bibliographies and proven sources as opposed to the term sources and references, However, the reference term has many and varied benefits that go into all areas of describing intellectual production, which proves that it has a basic value and added value that comes in the form of indispensable returns and guidance for workers in the library sector, publishing houses and publishers in all their spectrum.